2020
DOI: 10.3390/su12114666
|View full text |Cite
|
Sign up to set email alerts
|

How Risk Managers’ Psychological and Social Capital Promotes the Development of Risk-Management Capabilities

Abstract: The purpose of this study is to investigate the roles of risk managers’ psychological and social capital in risk-management capabilities (technical, business processes, and external resources) and the relationship between risk-management capabilities and management performance. This study treated organizational culture as a moderating variable. The research subjects (n = 1000) included top managers, general managers, and managers in various industries. This study found that risk managers’ positive psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(109 reference statements)
0
2
1
1
Order By: Relevance
“…However, the study results did not yield support for H3 since the positive relationship between internal social capital and SCRM capabilities was non-significant. These findings contradict previous studies such as Gligor and Holcomb (2012), Polyviou et al (2019) and Cui et al (2020), which emphasise the positive role of social capital in building SCRM capabilities. This can be explained by the supportive results for H7 of the mediating role of logistics capabilities, whereby internal social capital does not directly influence SCRM capabilities but it can also be utilised in building logistics capabilities, which can then enhance supply chain resilience and robustness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the study results did not yield support for H3 since the positive relationship between internal social capital and SCRM capabilities was non-significant. These findings contradict previous studies such as Gligor and Holcomb (2012), Polyviou et al (2019) and Cui et al (2020), which emphasise the positive role of social capital in building SCRM capabilities. This can be explained by the supportive results for H7 of the mediating role of logistics capabilities, whereby internal social capital does not directly influence SCRM capabilities but it can also be utilised in building logistics capabilities, which can then enhance supply chain resilience and robustness.…”
Section: Discussioncontrasting
confidence: 99%
“…Pinho (2011) added that relational capital provides access to novel sources of information necessary to build dynamic capabilities to cope with turbulent and unpredictable environment. Furthermore, Cui et al (2020) confirmed that risk managers' social capital play important roles in building corporate risk management capabilities. Similarly, Gao et al (2013) observed that cognitive capital is the most important social capital facet for building risk management capabilities compared to structural and relational capital.…”
Section: Theoretical Backgroundmentioning
confidence: 62%
“…Social capital is a relevant concept to firms' internationalization (Jones and Coviello 2005), and embodies the resources embedded in the network of relationships (Nahapiet and Ghoshal 1998). Taking into account some components of this concept, namely, managerial tie utilization, trust, and solidarity (e.g., Cui et al 2020), for instance, we suggest the relevant role that emotional intelligence and cultural intelligence may have in managers' interpersonal contacts and in building trust and solidarity.…”
Section: Introductionmentioning
confidence: 99%
“…Cui (2020), C.-H. Jin (2020) та J.-Y. Lee (2020) визначають місце соціального капіталу в управлінні корпоративними ризиками [21]. При цьому Н. Г. Діденко досліджує роль соціального капіталу у вирішенні управлінських проблем, а також процеси формування соціального капіталу в соціальних мережах [6]; Т. В. Боцян та Л. В. Зварич визначають організаційно-економічні особливості соціального капіталу в індустрії гостинності, що дозволили б відображати його в обліку [1]; О. Г. Яворська представляє авторську модель соціального капіталу підприємств сфери послуг, зокрема під час формування та розвитку мережевої форми організації в господарській практиці вітчизняного туристичного бізнесу [15].…”
unclassified